The Cross-School Teacher Team as a Site for Learning. Issue 2 (3rd April 2018) - Cederlund, Katarina
ABSTRACT: In policy and in initiatives from the Swedish National Agency for Education for enhancing professional development, there is currently a strong emphasis on teachers´ collaborative professional development. As previous research suggests that teachers may need to engage in various types of collaboration for learning, extended knowledge on different teacher teams for collaboration is needed. In this study, a Cross-School Teacher Team (CSTT) of teachers who shared pedagogical interests but worked in different municipalities was followed through observations, interviews, text-collections of logbook-reflections and digital communication. To examine what constitutes the CSTT as a site for learning and how this is shaped by as well as shaping the enabling and constraining arrangements, the empirical material was analysed through the lens of the theory of practice architectures. The results show how a CSTT can provide a complement to local teams for work integrated learning through diverse perspectives, a shared focus on specific and professional issues and a safe space for sharing and reflection. Internal and external transparency worked as a catalyst both for processes of reflection and transformation of local arrangements and practices. Knowledge of the practice architectures of the CSTT offer tools to elaborate upon alternative or complementary spaces for collaboration